DETERMINAN PERMINTAAN PARIWISATA INTERNASIONAL: STUDI WISATAWAN MANCANEGARA DI INDONESIA TAHUN 2013-2020 - Nairizi, Mirza Ahmad; Togar Laut, Lorentino; Sugiharti, Rr. Retno (Badan Perencanaan Pembangunan, Riset dan Inovasi Daerah Kota Magelang, 2024)
The tourism sector is one of the sectors that contributes the most to national foreign exchange earnings. However, trade in tourism services is still faced with a number of problems and challenges going forward. This can be seen from the comparison of the number of foreign tourist arrivals in Indonesia which shows that Indonesia's tourism market share is still limited and has not been able to compete in the international market. The purpose of this study is to determine and analyze the influence of the Tourism Consumer Price Index (TCPI), GDP per capita of the country of origin of foreign tourists, the Rupiah Exchange Rate against the currency of the country of origin of foreign tourists, and the Visit Visa Free Policy in Indonesia on international tourism demand in Indonesia in the 2013-2013 period. 2020. The variables used are variables that can influence international tourism demand according to previous researchers.The data used in this study is secondary data combining cross sections from 28 countries of tourist visitors and time series from 2013 to 2020. The data collection method was carried out through documentation sourced from the World Development Indicators, Bank Indonesia, and the Central Statistics Agency (BPS). The analytical method used is panel data with the help of Stata 17. The results of this study show that the GDP per capita of the country of origin of foreign tourists has a positive and significant effect on the demand for international tourism in Indonesia in 2013-2020. The rupiah exchange rate has a negative and significant effect on the demand for international tourism in Indonesia in 2013-2020, while the TCPI and Visit Visa Free Policy in Indonesia have no significant effect on demand for international tourism in Indonesia in 2013-2020.